Assessing the extent to which the future labor market needs traditional outputs from the higher education sector In a frame Proposed roadmap for the knowledge-based economy in the Syrian Arab Republic (A field study in the government banking sector) - طرابلسية, شيراز (Latakia University Journal - Economic and Legal Sciences Series, 2025)
The research started from the ambitious strategy of the Syrian Arab Republic for the year 2030 to reach a knowledge-based economy, and the survey addressed one of its pillars related to education and the acquisition of knowledge and skills. Accordingly, the study revolved around the following research question: Is the labor market, according to the new data, capable of consuming the traditional outputs of the higher education sector? The research concluded that the skills proposed to be included in the curricula according to the National Plan for Higher Education for the year 2010 are insufficient and do not meet the future needs of the local market according to the specific vision. Accordingly, one of the most important proposals was: rebuilding the curricula of the entire educational system according to the superior skills required by the Fourth Industrial Revolution to reach The desired economy.